2018
DOI: 10.1590/1806-9282.64.08.710
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in patients with advanced oral cancer who underwent mandibulectomy with or without bone reconstruction

Abstract: INTRODUCTION Malignant neoplasms of the head and neck, due to its anatomical location, can cause significant alterations in vital functions related to feeding, communication and social interaction of the affected patients. Objective To analyze the quality of life of patients with advanced malignant neoplasms of the oral cavity and submitted to radical operations with curative intent. Material and methods 47 patients with oral cavity squamous cell carcinoma (SCC), in stages III and IV, underwent surgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…The included studies involved a total of 1849 oral cancer patients of which at least 1308 were male, as one study did not report sex of patients (Vakil et al, 2012 ). Eleven studies only reported mean or median age with SD and did not mention range (Agarwal et al, 2014 ; Bekiroglu et al, 2011 ; Gu et al, 2021 ; Hoene et al, 2021 ; Larson et al, 2021 ; Rogers et al, 2004 ; Rogers & Lowe, 2020 ; Seferin et al, 2022 ; Soares et al, 2018 ; Wu et al, 2020 ; Zhang et al, 2020 ). One study did not mention age of patients (Vakil et al, 2012 ) and three studies categorised patients in age groups without further details about mean and SD (Rogers & Lowe, 2020 ; Yue et al, 2018 ; Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies involved a total of 1849 oral cancer patients of which at least 1308 were male, as one study did not report sex of patients (Vakil et al, 2012 ). Eleven studies only reported mean or median age with SD and did not mention range (Agarwal et al, 2014 ; Bekiroglu et al, 2011 ; Gu et al, 2021 ; Hoene et al, 2021 ; Larson et al, 2021 ; Rogers et al, 2004 ; Rogers & Lowe, 2020 ; Seferin et al, 2022 ; Soares et al, 2018 ; Wu et al, 2020 ; Zhang et al, 2020 ). One study did not mention age of patients (Vakil et al, 2012 ) and three studies categorised patients in age groups without further details about mean and SD (Rogers & Lowe, 2020 ; Yue et al, 2018 ; Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study did not mention age of patients (Vakil et al, 2012 ) and three studies categorised patients in age groups without further details about mean and SD (Rogers & Lowe, 2020 ; Yue et al, 2018 ; Zhang et al, 2020 ). Studies were mainly conducted in China (Fang et al, 2014 ; Fang et al, 2013 ; Gu et al, 2021 ; Li et al, 2013 ; X. Li, Sun, & Guo, 2016 ; W. Li, Zhang et al, 2016 ; Wu et al, 2020 ; Yan et al, 2017 ; Yang et al, 2014 ; Yuan et al, 2016 ; Yue et al, 2018 ; Zhang et al, 2020 ; Zhang et al, 2013 ), followed by India (Agarwal et al, 2014 ; Ghai et al, 2021 ; Sakthivel et al, 2017 ; Vora et al, 2017 ), the United Kingdom (Bekiroglu et al, 2011 ; Devine et al, 2001 ; Rogers et al, 2004 ; Rogers & Lowe, 2020 ), Brazil (Seferin et al, 2022 ; Soares et al, 2018 ), the United States (Larson et al, 2021 ; Ochoa et al, 2021 ), Germany (Hoene et al, 2021 ) and Pakistan (Vakil et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…El pilar terapéutico fundamental en el COCE es la resección quirúrgica, la cual, debido a su ubicación anatómica, causa alteraciones significativas en las funciones vitales relacionadas con la alimentación, la comunicación y la interacción social de los pacientes afectados (24).…”
Section: Etiopatogenia Del Coce En Pacientes Jóvenesunclassified